PENGARUH STRUKTUR MODAL, PERTUMBUHAN PENJUALAN DAN LIKUIDITAS TERHADAP PROFITABILITAS - Sari, Ratih Komala; -, Sunaryo; Bandawaty, Euis (AKRUAL : Jurnal Akuntansi dan Keuangan, 2025)
This study aims to examine the effect of capital structure, sales growth, and liquidity on profitability. The independent variables in this study are capital structure as measured by the Debt to Equity Ratio (DER), sales growth, and liquidity as measured by the Current Ratio (CR). The dependent variable in this study is profitability as measured by Return on Assets (ROA). The population in this study consists of food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2024 period. The sample was selected using purposive sampling, resulting in 18 companies with a five-year research period and a total of 90 observations. Hypothesis testing was conducted using panel data regression analysis. The results of this study show that capital structure have a significant negative effect on profitability, sales growth have a significant positive effect on profitability, and liquidity does not have a significant effect on profitability.